Analisis Strategi Pencegahan Cybercrime Berdasarkan UU ITE Di Indonesia (Studi Kasus: Penipuan Pelanggan Gojek) - Reza Hikmatulloh; Evy Nurmiati (Kosmik Hukum, 2020)
Cybercrime can be defined as illegal activities with computer intermediaries that can be carried out through global electronic networks. In computer networks such as the internet, the problem of crime is becoming increasingly complex due to its wide scope. The purpose of this study is to see what strategies are suitable for preventing cybercrime actions via cell phones based on the ITE Law in Indonesia. The data analysis method used in this study is to use routine activity theory. Cohen and Felson's incidence that crime against crime is related to three variables, namely someone who is motivated, the target who is the target, and the absence of protection from the target (absence of a capable guard). The suggestion is that Gojek provides education about awareness in this fraud case. Gojek appeals to users on their social media to be more careful in trusting information. In addition, the government should not only give warnings to its users as a form of vigilance, but the government should be more optimal in giving more effort.Keywords: Cybercrime, ITE Law, Routine Activity Theory